FORMULASI MIKROENKAPSUL OLEORESIN KAYUMANIS (Cinnamon burmanni) DAN CENGKEH (Caryophillus aromaticus Linn) - Arifan, Fahmi; Wikanta, Deddy Kurniawan (Universitas Diponegoro, 2012)
Product development spices such as cinnamon and cloves in the form of oleoresin microcapsules cinnamon and cloves that can be used as a natural preservative because of its potential as an antioxidant and antimicrobial as well as a flavoring agent (agent taste) in food products. In this research, formulation of microcapsules to obtain microcapsules pleoresin cloves and cinnamon. Optimal extraction results obtained at 50 ° C, pressure of 350 bar, the efficiency of clove and cinnamon bark amounted to 17.24% and 1.16% of khromatography Cinnamaldehye analysis of cinnamon was 96.7%, moderate levels of eugenol clove 72, 08%. Terstabil emulsion composition with a ratio of lecithin; gum arabic; malto dextrin and CMC (10; 90, 10, 10), emulsion terstabil microcapsules made ​​with two formulas, formula A with clove oleoresin composition is more dominant, and the composition of formula B with composition oleoresin microcapsules cinnamon bark is more dominant, the results for the microencapsulation formula A 8 (1:4) was 85.98% and B8 formula (4:1) 89.13%. Key word : oleoresin clove, cinnamon-microencapsulated